No Deep Pockets: Some stylized results on firms' financial constraints - Silva, Filipe (2009)
This paper is a brief survey of recent empirical work on financial constraints faced by firms. It is organized as a series of stylized results which mirror what is generally understood about severity of financial constraints and effects that they have upon firms. This survey shows that (a) the financial constraint is a widespread key concern for firms, hindering their ability to carry out their optimal investment and growth trajectories and (b) the severity of such constraints depends on institutional and firm specific characteristics, as well as on the nature of investment projects